2012
DOI: 10.1371/journal.pntd.0001677
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Giardia duodenalis Assemblage B Infection and Association with Underweight in Rwandan Children

Abstract: Background Giardia duodenalis is highly endemic in East Africa but its effects on child health, particularly of submicroscopic infections, i.e., those below the threshold of microscopy, and of genetic subgroups (assemblages), are not well understood. We aimed at addressing these questions and at examining epidemiological characteristics of G. duodenalis in southern highland Rwanda. Methodology/Principal Findings In 583 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
112
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 51 publications
(64 reference statements)
18
112
1
3
Order By: Relevance
“…G. intestinalis infection was also observed to influence nutritional status in northeastern Brazil [31][32][33]. In Rwanda, G. intestinalis infection was identified as a predictor of being underweight and severe malnutrition [30]. Similarly, giardiasis was also a strong predictor of low HAZ in Colombia and Iran, and has also been shown to be significantly associated with lower body weight, serum zinc levels, and serum iron levels in Egypt [11,13,34].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…G. intestinalis infection was also observed to influence nutritional status in northeastern Brazil [31][32][33]. In Rwanda, G. intestinalis infection was identified as a predictor of being underweight and severe malnutrition [30]. Similarly, giardiasis was also a strong predictor of low HAZ in Colombia and Iran, and has also been shown to be significantly associated with lower body weight, serum zinc levels, and serum iron levels in Egypt [11,13,34].…”
Section: Discussionmentioning
confidence: 91%
“…In many regions, it is possible that the STH control strategies, which are performed without parasitological diagnoses, are contributing to the neglect of basic laboratory infrastructure and the diversion of personnel training away from parasitological diagnoses. When used in cross-sectional studies, molecular diagnostic techniques generally yield higher prevalence rates due to their improved sensibility, suggesting that some infections are not detected by light microscopy [30]. However, the higher cost of diagnostic PCR prohibits its use at the community level in many developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study in Australia found assemblage A to be associated with diarrhea, while assemblage B was found mainly in asymptomatic children (100). In a study among Rwandan children, assemblage A was associated with vomiting and abdominal pain (101). There are also examples of studies where clinical differences associated with the two assemblages were not identified (102,103).…”
Section: Giardiamentioning
confidence: 94%
“…This includes neglected tropical diseases (NTDs). The geohelminths (soil-transmited helminths [STHs]) and the intestinal G. duodenalis parasite alone infect hundreds of millions of people in SSA [32,33].…”
Section: Epidemiologymentioning
confidence: 99%